Pengaruh Implementasi Kebijakan Netralitas PNS Terhadap Kualitas Pelayanan Publik di Dinas Tenaga Kerja Kota Manado - Kasmayuda, Fikran; Lengkong, Florence Daicy Jetty (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: Policy neutrality of civil servants is expected to improve the quality of public services in the government bureaucracy. But in fact still be seen attitudes and behavior of civil servants who have little or no neutral from political party influence. On that basis, this study is intended to answer the question how far the influence of the implementation of civil service neutrality policy toward public service in the Department of Labor Manado City. This study uses quantitative methods. Sources of data / research respondents were as many as 60 people consisting of 30 employees Manado City Department of Labor, and 30 community members who never got the public service in the Department. Collecting data using questionnaires and assisted with interviewing techniques. The analysis technique used is regression analysis and product moment correlation. Based on the analysis of the data showed: (1) the regression coefficient of the variable implementation of civil service neutrality policy on public service quality is significant posifive and (2) the correlation coefficient and the coefficient of determination of policy implementation variables neutrality of civil servants on the quality of public services is high and significant. Based on the results of the data analysis concluded that the implementation of civil service neutrality policy had a positive effect and the significant determinants of the quality of public services. Keywords: Implementation of policy, neutrality of civil servants, the Public Service.